PENGARUH KINERJA PERUSAHAAN, STRUKTUR MODAL TERHADAP KUALITAS LABA PADA PERUSAHAAN YANG TERDAFTAR DI BEI (Studi Empiris Pada Perusahaan Manufaktur Periode 2018-2020) - Ana Silva Anggraini; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2022)
This study aims to determine the effect of company performance and capital structure on earnings quality in companies listed on the BEI, to determine the effect of company performance on earnings quality in companies listed on the BEI, to determine capital structure on earnings quality in companies listed on the BEI. The results of the sampling resulted in 27 companies in the period 2018 to 2020. The data analysis method in this study is multiple linear analysis with spss23.The results of the research hypothesis test show that simultaneously profitability and capital structure have no effect on earnings quality. Profitability partially has a negative and significant effect on earnings quality. Capital structure has no effect on earnings quality.Keywords: Profitability, Capital Structure, Earnings Quality